A minimalist fluorescent probe for differentiating Cys, Hcy and GSH in live cells. Issue 1 (8th October 2015) - Zhang, Huatang; Liu, Ruochuan; Liu, Jie; Li, Lin; Wang, Ping; Yao, Shao Q.; Xu, Zhengtao; Sun, Hongyan
Abstract : A simple and versatile probe was discovered for discriminating between different thiol species with the use of CTAB (cetyl trimethylammonium bromide). Abstract : A simple molecule, tetrafluoroterephthalonitrile (4F-2CN), was discovered to be an efficient fluorescent probe for detecting biological thiol species. The probe responded to Cys and emitted strong green fluorescence, whereas it reacted with Hcy/GSH and generated blue fluorescence. Addition of CTAB (cetyl trimethylammonium bromide) was observed to alter the fluorescence color of the reaction product of 4F-2CN and Hcy (from blue to green), but no alteration of the fluorescence color occurred for Cys and GSH. For the very first time, cell imaging experiments showed that the three commonly occurring thiols (Cys/Hcy/GSH) could be differentiated using a single fluorescent probe. In addition, the reaction product of 4F-2CN and Cys exhibits two-photon properties, offering a potentially useful tool for tissue imaging studies. To the best of our knowledge, 4F-2CN is currently the smallest fluorescent probe for thiol detection. We envision that this new and versatile probe will be a useful tool for further elucidating the roles of thiols in biology.